UNSETTLING EUROPEAN EPISTEMOLOGIES - MAPPING THE CONTOURS OF PARADIGMS FROM THE SOUTH - Nair, Harikrishnan Gopinathan (Nomos: Revista do Programa de Pós-Graduação em Direito da UFC, 2018)
I would like to talk about Epistemologies from the South, or Southern epistemologies, or Epistemologias sur-sur. Although I was interested in the politics of knowledge production, distribution, and consumption for quite a few years now, I became involved in this subject three years ago, when I came across a study by Claude Alvares – an Indian scholar from Goa, which is a former Portuguese colony on the West coast of India.